Pengaruh Budaya Organisasi terhadap Perilaku Akuntansi dalam Pengelolaan Keuangan - Prasetyo, Hendra Dwi (PUTRA JAWA PUBLISHER, 2024)
This study aims to analyse the influence of organisational culture on accounting behaviour in financial management. Organisational culture has an important role in shaping values, norms and habits that influence accounting decision-making in a company. This study uses a quantitative approach by collecting data through a survey involving accountants and financial managers from various companies. The results show that a strong organisational culture, with values of transparency, integrity and accountability, significantly contributes to improving the quality of financial management. In contrast, a weak organisational culture tends to lead to less ethical and inefficient accounting behaviour. The implications of these findings provide insights for company leaders to build an organisational culture that supports better financial management.